Bilateral Telencephalic Gliomatosis Cerebri in a Dog - Mario Ricciardi; Antonio De Simone; Pasquale Giannuzzi; Maria Teresa Mandara; Alice Reginato; Floriana Gernone (Case Reports in Veterinary Medicine)
An 8-year-old intact male Lagotto Romagnolo was presented with forebrain signs. Neuroanatomic localization was diffuse prosencephalon. MRI revealed diffuse, bilateral, and symmetric T2 and FLAIR hyperintensities in the parieto-occipital white matter and corpus callosum. No mass effect or contrast enhancement was noted. Analysis of cerebrospinal fluid revealed normal protein content and mild mononuclear pleocytosis. Atypical cells were not identified. 15 days later because of the worsening of clinical condition the patient was euthanized upon owner’s request. Neuropathological investigations were consistent with gliomatosis cerebri (GC). Such an unusual imaging pattern appeared similar to some cases of human GC and to a previous reported case in a dog, suggesting a possible repeatable imaging findings for this rare brain neoplasm. GC should be included in the MRI differentials for diffuse bilateral white matter signal changes and specific MRI findings described in this report may help in reaching a presumptive diagnosis of this tumor.